The Chinese guidelines for the diagnosis and treatment of pancreatic neuroendocrine neoplasms (2020). Issue 1 (March 2021) - Wu, Wenming; Chen, Jie; Bai, Chunmei; Chi, Yihebali; Du, Yiqi; Feng, Shiting; Huo, Li; Jiang, Yuxin; Li, Jingnan; Lou, Wenhui; Luo, Jie; Shao, Chenghao; et al.
Abstract : Abstract: Pancreatic neuroendocrine neoplasms (pNENs) are highly heterogeneous, and the management of pNENs patients can be intractable. To address this challenge, an expert committee was established on behalf of the Chinese Pancreatic Surgery Association, which consisted of surgical oncologists, gastroenterologists, medical oncologists, endocrinologists, radiologists, pathologists, and nuclear medicine specialists. By reviewing the important issues regarding the diagnosis and treatment of pNENs, the committee concluded evidence-based statements and recommendations in this article, in order to further improve the management of pNENs patients in China.